Can bacteria fly? - bacteriological assessment of common fly (Musca domestica) as a potential carrier for public health epidemics - Tabassum, Nuzhat; Chowdhury, Tonuka Tunazzina (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology and Bachelor of Science in Microbiology, 2023.